The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ejsobi.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of long-term water level draw-down on microbial biomass: A comparative study from two peatland sites with different nutrient status

Abstract: The impact of long-term water level draw-down on general microbial biomass: a comparative study from two peatland sites with different nutrient status

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
3
11
0
1
Order By: Relevance
“…Total lipids of the freeze-dried samples were extracted and fractionated into neutral, glyco-, and phospholipids, and the phospholipid fraction was analyzed as explained before (Bligh and Dyer 1959; Mpamah et al . 2017). The amount (µg fatty acids g −1 dw) of BrFA (sum of i14:0, i15:0, a15:0, i16:0, i17:0, a17:0 and i18:0) was used as a biomarker of living bacterial biomass.…”
Section: Methodsmentioning
confidence: 99%
“…Total lipids of the freeze-dried samples were extracted and fractionated into neutral, glyco-, and phospholipids, and the phospholipid fraction was analyzed as explained before (Bligh and Dyer 1959; Mpamah et al . 2017). The amount (µg fatty acids g −1 dw) of BrFA (sum of i14:0, i15:0, a15:0, i16:0, i17:0, a17:0 and i18:0) was used as a biomarker of living bacterial biomass.…”
Section: Methodsmentioning
confidence: 99%
“…In fens, members of the phyla Proteobacteria and Bacteroidetes have been shown to be particularly sensitive to drought, as well as protists of the phylum Rhizaria and ectomycorrhizal fungi (Peltoniemi et al, 2012;Potter et al, 2017). Drainage of fens has been shown to increase microbial activity and modify the active microbial community (Strakova et al, 2011;Mpamah et al, 2017); this is driven by a change in litter type (Peltoniemi et al, 2012) and exhibits a nonlinear response to water-table drawdown (Jassey et al, 2018). Peltoniemi et al (2015) examined the interaction of warming and drainage status on microbial activity in two boreal fens.…”
Section: Wider Microbial Communitymentioning
confidence: 99%
“…Many studies have shown that drainage affects C and N mineralization processes in peatland, helping to shift it between serving as a sink or source (Chen et al, 2012; Chimner et al, 2017; Laine, Makiranta, et al, 2019; Zhang et al, 2020). Fluctuation in the watertable can directly affect soil biogeochemical properties, including soil physical and chemical properties, soil substrate, microbial community, and enzyme activity, ultimately altering GHG emissions (de Vries et al, 2018; Mpamah et al, 2017; Swails et al, 2018; Wen et al, 2019). DOC and TDN concentrations reflect the balance between SOM production and consumption by microbes, which decompose DOC and TDN into GHG (van den Berg et al, 2012).…”
Section: Discussionmentioning
confidence: 99%